2014
DOI: 10.1038/srep05920
|View full text |Cite
|
Sign up to set email alerts
|

Laundering durable antibacterial cotton fabrics grafted with pomegranate-shaped polymer wrapped in silver nanoparticle aggregations

Abstract: To improve the laundering durability of the silver functionalized antibacterial cotton fabrics, a radiation-induced coincident reduction and graft polymerization is reported herein where a pomegranate-shaped silver nanoparticle aggregations up to 500 nm can be formed due to the coordination forces between amino group and silver and the wrapping procedure originated from the coincident growth of the silver nanoparticles and polymer graft chains. This pomegranate-shaped silver NPAs functionalized cotton fabric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 55 publications
(61 reference statements)
1
42
0
Order By: Relevance
“…The hydroxyl groups of cellulose chains on the cotton surface form coordination bonds with the AgNPs, but the quantity of the coordination bonds is limited by the three-dimensional shapes of the cotton fiber and AgNPs. As reported in a number of papers [38,[41][42][43][44][45][46] using the binder of the modified chitosan, both the quantity (chitosan chains wrapping on the Ag NP surface) and the bond strength (amino groups are stronger than hydroxyl groups) of the coordination bonds with Ag NP increased, resulting in a stronger adsorption of the AgNPs on the cotton surface. Figure 9 shows the TGA data of the original cotton, the modified cotton fabrics before and after 30 laundering cycles.…”
Section: Laundering Durabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The hydroxyl groups of cellulose chains on the cotton surface form coordination bonds with the AgNPs, but the quantity of the coordination bonds is limited by the three-dimensional shapes of the cotton fiber and AgNPs. As reported in a number of papers [38,[41][42][43][44][45][46] using the binder of the modified chitosan, both the quantity (chitosan chains wrapping on the Ag NP surface) and the bond strength (amino groups are stronger than hydroxyl groups) of the coordination bonds with Ag NP increased, resulting in a stronger adsorption of the AgNPs on the cotton surface. Figure 9 shows the TGA data of the original cotton, the modified cotton fabrics before and after 30 laundering cycles.…”
Section: Laundering Durabilitymentioning
confidence: 99%
“…The modified fabrics exhibited durable antimicrobial effect after 10 washing cycles (BR > 99 %). Li et al [41] reported a novel graft polymerization method using 2-aminoethyl methacrylate as the monomer. Because the primary amine groups in the monomer form coordination bonds with the Ag ions, the resulting polymer tightly wraps the AgNPs, and simultaneously adheres to the fiber surface via the hydrogen bonds between the ester and the hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we successfully fabricated novel superhydrophobic fabrics272829, antibacterial fabrics3031, and self-cleaning fabrics32 with excellent washing durability and abrasion resistance via gamma ray irradiation-induced graft polymerization of functional monomers and components. H. Lin et al .…”
mentioning
confidence: 99%
“…It is also potential that the attachment of AgNPs onto fabrics is by AgNPs‐amino groups interaction. An observation was carried out for cotton fibers incorporated with AgNPs . X‐ray photoelectron spectroscopy investigation confirmed that there was the coordination force of the amino group in the monomer with AgNPs.…”
Section: Deposition Mechanismmentioning
confidence: 99%